2021
DOI: 10.1057/s41599-021-00830-w
|View full text |Cite
|
Sign up to set email alerts
|

Predicting effectiveness of countermeasures during the COVID-19 outbreak in South Africa using agent-based simulation

Abstract: COVID-19 has spread rapidly around the globe. While there has been a slow down of the spread in some countries, e.g., in China, the African continent is still at the beginning of a potentially wide spread of the virus. Owing to its economic strength and imbalances, South Africa is of particular relevance with regard to the drastic measures to prevent the spread of this novel coronavirus. In March 2020, South Africa imposed one of the most severe lockdowns worldwide and subsequently faced the number of infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Niwa et al's ( 2021 ) study showed that mild and continuous lockdown could have better containment outcomes than strong and intermittent ones. Although extended lockdown did have remarkable impacts on reductions in infections and deaths (Kersting et al, 2021 ), a country or region should make trade‐offs between the control results of COVID‐19 spread and the economic development and social well‐being.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Niwa et al's ( 2021 ) study showed that mild and continuous lockdown could have better containment outcomes than strong and intermittent ones. Although extended lockdown did have remarkable impacts on reductions in infections and deaths (Kersting et al, 2021 ), a country or region should make trade‐offs between the control results of COVID‐19 spread and the economic development and social well‐being.…”
Section: Discussionmentioning
confidence: 99%
“…Wearing facemasks and 50% social isolation adherence was identified as the best scenario to achieve the balance between preserving lives and minimizing negative economic impact. Kersting et al's ( 2021 ) study proved that strict measures were an effective way of buying time to expand healthcare system capacities and improve prevention measures.…”
Section: Discussionmentioning
confidence: 99%
“…Isabel Briggs Myers and her mother, Kathryn Briggs, are devoted to studying the concepts of Carl Jung, a Swiss psychiatrist ( Kersting et al, 2021 ). People prefer to rely on variables such as parental advice and emulation when choosing a job path rather than pursuing their own interests.…”
Section: Proposed Methodologymentioning
confidence: 99%
“…Agent-based simulations are simulations in which a number of agents, each with their own thread, code, and state, interact in a virtual environment. They play an increasingly important role in the social sciences [6,24,26,27,36,41,42,44,63,69,70], sustainability research [14,20,46,47,50,52,59,60], economics and finance [10,15,25,29,58,71,73], epidemiology [1,40,43,49,64,66], population dynamics [11,21,38], and entertainment (gaming [5]). Agent-based simulations have become important tools to help make decisions of monumental importance to modern society.…”
Section: Introductionmentioning
confidence: 99%